Adaptive Educational Management through PDIA to Enhance Psychological Resilience among Vocational Students - Aqilla Yumna Ilma Izzati; Luthfiyah Nurlaela; Dewi Fitrotus Sa’diyah (International Journal of Economics and Management Research, 2026)
This study aimed to analyze the application of education governance using the Problem-Driven Iterative Adaptation (PDIA) method to reinforce psychological endurance among vocational secondary school learners. The focus centered on identifying how institutional governance practices respond to learning demands, psychological exposure, and post-pandemic transition barriers within vocational education contexts. The research employed a qualitative case research pattern implemented in three state vocational secondary schools located in East Java, Indonesia. Participants included headmasters, educators, counseling personnel, and learners. Information acquisition was conducted through semi-structured dialogues, instructional monitoring, and file review. Data processing applied thematic interpretation supported by numerical tabulation to capture patterns across institutional practices and learner responses.  Results:  The findings showed that PDIA-oriented governance enabled institutions to recognize context-based psychological issues, formulate stepwise actions, and repeatedly adjust policies. Learners demonstrated growth in emotion control, personal assurance, coping capacity, and learning participation following the implementation of iterative governance practices within school management processes.  Novelty: The originality of this research lies in merging PDIA previously implemented within public administration and educator supervision into institutional education governance. This integration offers a structured governance pathway to methodically reinforce learner psychological endurance within vocational education environments, extending PDIA application beyond its conventional administrative scope.